SERUM CHOLESTEROL IN IMMUNOSTIMULATED MICE DURING INDUCED HEPATITIS B - GOLD , V. JASMIN; VARDHANI, V. VIVEKA (The Bioscan, 2013)
The level of serum cholesterol showed considerable decrease during the entire experimental period (1 to 5 days) of infection in all experimental groups (immunostimulated + vaccinated) of mice when compared with controls (group c, unimmunostimulated + unvaccinated; group I, immunostimualted). The decrease of serum cholesterol was influenced by the retained Gen Vac B Hbs Ag infective virus and the immunological damage caused by the infectious viral organisms within the host system.